Effect of Drying Method on Levels of Antioxidant Activity, Total Flavonoid Levels, and Total Phenol Levels in Ethanol Extract of Bawang Dayak (Eleutherine americana) Leaves - Sri Wahdaningsih; Shoma Rizkifani; Eka Kartika Untari; William Rinaldi (Majalah Obat Tradisional, 2023)
The drying process can affect the content of seconder metabolites such as flavonoids and phenols in plants. The content of flavonoids and phenols plays an important role in the antioxidant activity of a plant. This study aims to determine the effect of drying methods using sunlight and oven on antioxidant activity, total flavonoids, and total phenols. Measurement of antioxidant activity using the DPPH method with vitamin C as a standard, total flavonoid levels using quercetin as a standard, and total phenol using gallic acid as a standard were measured using a UV-Vis spectrophotometer. The results of antioxidant activity (IC50)by sun drying and oven respectively were 123 ppm and 152 ppm, total flavonoid content by sun drying and oven respectively were 22.5% and 20.698%, and total phenol content by sun drying and oven respectively amounted to 37.35% and 36.648%. The conclusion is that the sun-drying method has antioxidant activity, total flavonoids, and total phenol levels which are greater than the oven-drying method.